A avaliação no sistema de ensino do Espírito Santo: docência e discência premidas pelos resultados - Pereira, Wagner Miguel (2023)
In the educational context in recent decades, we have experienced an abundance of external and standardized assessments and social control of teaching through measurement mechanisms, with the declared goal of achieving quality indicator targets. It is, therefore, an educational model associated with the concept of "accountability," as defined by Afonso (2009), which means being accountable and responsible for the outcomes. By establishing Ordinance No. 064-R on May 24, 2017, the Department of Education of the State of Espírito Santo instituted the Sicaeb - Capixaba Basic Education Assessment System. This intensified the implementation of external assessments known as Paebes TRI, which were conducted in the three school terms between 2015 and 2019, with the stated goal of improving the Ideb of the state education system in Espírito Santo. In response to this, we conducted an analysis to assess the results achieved by high schools in Greater Vitória from 2015 to 2019. The goal of this study was to understand if it is possible to enhance the mathematics learning of high school students in the state of Espírito Santo through the intensification of large-scale assessments. Regarding the research methods, we used a literature review of scientific articles, books, theses, and dissertations to examine relevant literature on the topic and objectives of the study. In addition, primary data from the Department of Education's statistical database and Paebes TRI Reports were utilized. Although quantitative data were used, the analysis conducted was qualitative since it aimed to problematize them and identify their implications for school practices related to assessment.The development of the research was directly impacted by the Covid-19 pandemic, which led us to opt for an exploratory research approach based on data that did not require visits to schools and the use of other in-person techniques. The results indicated the need for a broader and more integrated approach to assessment in basic education, which considers not only test/exam results but the quality of the educational process. As a result of the research findings, an educational product was created, a blog, and a YouTube channel focused on scientific dissemination related to educational assessment, with an emphasis on the Capixaba movement.